Peningkatan Hasil Belajar pada Pembelajaran Tematik Terpadu Menggunakan Model Example Non Example di Sekolah Dasar - Cahyanda, Bella; Yunisrul, Yunisrul (Universitas Negeri Padang, 2021)
The purpose of this research is to describe the planning, implementation and improvement learning outcomes of students using a Example Non Example model in integrated thematic learning in grade V Elementary School. In this study applying the type of PTK research uses qualitative and quantitative approaches. Where this research was conducted on class V SDN 11 Campago Guguk Bulek Kota Bukittinggi totaling 26 people consisting of 9 male students and 17 female students. The results of the study in the first cycle of learning outcomes reached a percentage of completeness of 65,5% (need guidance category) with an average value of 75 (enough category) increased in the second cycle percentage of completeness 92% (very good category) with an average achievement of 90 (very good category).